PENGARUH BUDAYA ORGANISASI TERHADAP KOMITMEN ORGANISASIONAL DAN ORGANIZATIONAL SILENCE PADA PT. PLN (PERSERO) RAYON DENPASAR - Dewi, I Gusti Ayu Ketut Ratna; Surya, Ida Bagus Ketut (E-Jurnal Manajemen, 2017)
The purpose of this study was to investigate the influence of organizational culture on organizational silence and organizational commitment at PT. PLN (Persero) Rayon Denpasar. Samples taken as many as 52 respondents. The samples in this study using purposive saturated or census sampling technique. The data collection is done by distributing questionnaires using 5-point Likert scale to measure 30 items pernyataan. The  analysis technique is Path analysis. The analysis showed that organizational culture positive significant effect on organizational commitment, organizational culture significant effect negatively to organizational silence, organizational commitment negatively significant effect on organizational silence on PT. PLN (Persero) Rayon Denpasar. For the PT. PLN (Persero) Rayon Denpasar more attention to indicators of adaptation to the organizational culture variables and indicators acquiescent silence silence on organizational variables to increase organizational commitment and reduce organizational behavior silence.
Keywords: organizational culture; organizational commitment; organizational silence